Construction of pad foundation - Noor Hisham, Muhammad Hazim (Universiti Teknologi MARA, Perak, 2019)
Pad foundation that also known as pad footing usually been used in the construction of a building as supporting component to the load of the building. The pad foundation function as a transmitting element to transmit all the load from the building to the ground. The main objective of this research are to investigate the flow method of constructing the pad foundation, the machineries that been use during the construction of pad foundation and determine the problem and solution during pad construction. Next, all the data had been collected through an observation during the site visit, taking some photo, having an interview session with the project manager and do some document reviews for the data.